2016
DOI: 10.1039/c6ob00693k
|View full text |Cite
|
Sign up to set email alerts
|

Anthranilic acid-containing cyclic tetrapeptides: at the crossroads of conformational rigidity and synthetic accessibility

Abstract: Each amino acid in a peptide contributes three atom units to main-chains, hence natural cyclic peptides can be 9, 12, 15, …. ie 3n membered-rings, where n is the number of amino acids. Cyclic peptides that are 9 or 12-membered ring compounds tend to be hard to prepare because of strain, while their one amino acid homologs (15-membered cyclic pentapeptides) are not conformationally homogeneous unless constrained by strategically placed proline or D-amino acid residues. We hypothesized that replacing one genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 80 publications
4
17
0
Order By: Relevance
“…Importantly, NMR studies revealed the solution structure of these CTPs to be conformationally homogeneous and the structure of 4 to be in agreement with its crystal structure. This all‐ trans conformation appears to be independant of N ‐methylation, at least in the position prior to 2‐Abz, and the stereoconfiguration of the additional residues, in accordance with the recent solution structure calcuations of Xin and Burgess The predictable and versatile nature of these 2‐Abz CTPs provides significant merit as scaffolds for rational design. Interestingly, the 2‐Abz containing cyclic pentapeptide, cycloaspeptide A, demonstrated four trans ‐amides and a single cis ‐amide bond preceeding one of the two N ‐methylated residues .…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Importantly, NMR studies revealed the solution structure of these CTPs to be conformationally homogeneous and the structure of 4 to be in agreement with its crystal structure. This all‐ trans conformation appears to be independant of N ‐methylation, at least in the position prior to 2‐Abz, and the stereoconfiguration of the additional residues, in accordance with the recent solution structure calcuations of Xin and Burgess The predictable and versatile nature of these 2‐Abz CTPs provides significant merit as scaffolds for rational design. Interestingly, the 2‐Abz containing cyclic pentapeptide, cycloaspeptide A, demonstrated four trans ‐amides and a single cis ‐amide bond preceeding one of the two N ‐methylated residues .…”
Section: Resultssupporting
confidence: 81%
“…Interestingly, 3 and 4 bear different orientations of the peptide bond at d ‐Phe (Figure ), a consequence of the steric effect from N ‐methylation. The bond orientation observed for 3 is in accordance with solution conformations calculated for similar non‐ N ‐methylated CTPs by Xin and Burgess . The space‐fill models of 3 and 4 (Figure S7) demonstrate the lack of available space for N ‐methylation in the geometry of 3 resulting in the observed bond flipping in 4 .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations